Recognizing the sustainable development on regional level with the example of Dravinja valley - Vovk Korže, Ana (Journal for Geography, 2014)
Recognizing sustainable development on regional level is the key for planning of the activities that base on ecosystem protection, people connection and in inclusion of all sectors into progress, as well as on the self- sufficiency with the inclusion of the local people.  This is why the research about knowing the sustainable development in Dravinja valley was made. During last seven years have been many projects on the sustainability base performed in this area. Research included 250 people, questionnaires were returned from 100 people. Questions were attached into the topic of the evaluation of the cultural and natural heritage influence, multi-purposeful use of rural areas, human resources investments, investments into innovation, investments into qualitative farm production, on sustainable management with natural resources, preserving of the cultural landscape and importance of environment protection. People that answered questionnaires live in municipalities Zreče, Slovenske Konjice, Oplotnica, Vitanje, Poljčane, Makole and Majšperk. Findings show that people do not give the greatest importance on money and comfort, but also on active participation and preserved nature. The biggest parts of support go on creation of green workplaces, improvement of life in rural areas and increasing of the Dravinja valley recognition with own brand.